2022
DOI: 10.1097/md.0000000000032010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of esketamine on analgesia and postpartum depression after cesarean section: A randomized, double-blinded controlled trial

Abstract: Background: The aim of this randomized double-blind placebo controlled clinical trial was to investigate the effects of different doses of esketamine combined with sufentanil for postoperative intravenous controlled analgesia after cesarean section and the incidence of postpartum depression. Methods: One hundred and sixty patients undergoing elective cesarean section, with a singleton term pregnancy and American Society of Anesthesiologists physical status II were selected. All patients were treated by a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Another recent study showed that esketamine alleviated short-term depressive symptoms after laparoscopic modified radical hysterectomy ( 19 ). Furthermore, several studies also suggested that the use of esketamine prevented postpartum depressive symptoms after cesarean section ( 31 , 32 ). A recent study showed that intraoperative esketamine infusion improved postoperative sleep disturbance, but not depression symptoms, after gynecological laparoscopy ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study showed that esketamine alleviated short-term depressive symptoms after laparoscopic modified radical hysterectomy ( 19 ). Furthermore, several studies also suggested that the use of esketamine prevented postpartum depressive symptoms after cesarean section ( 31 , 32 ). A recent study showed that intraoperative esketamine infusion improved postoperative sleep disturbance, but not depression symptoms, after gynecological laparoscopy ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that esketamine is fast and effective in reducing the onset of postnatal depression with a low incidence of adverse events. Wang et al [19] . observed that esketamine combined with sufentanil improved postoperative analgesia in patients after elective caesarean section and reduced the dosage of sufentanil and the incidence of PPD and postoperative nausea and vomiting at 1 and 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the use of esketamine are even scarcer, with only 4 RCTs (n = 56-210) examining the role of systemic esketamine for cesarean pain but with substantially different study designs, primary outcomes, and esketamine doses. [4][5][6][7] Overall, the studies are, however, promising, suggesting that esketamine is associated with reduced intraoperative pain, reduced postoperative pain, and the need for lower doses of local anesthetic for spinal anesthesia. Two of the studies 6,7 also considered postnatal depression given the increasing recognition of esketamine as an effective treatment for depression, but the effects here were nonconsistent, potentially reflecting the short period of use.…”
mentioning
confidence: 99%
“…A meta-analysis of 20 RCTs (1737 patients) assessing the more commonly used racemic ketamine during cesarean delivery reported decreased postoperative pain and analgesia use, although the effect on intraoperative pain was not reported. Studies investigating the use of esketamine are even scarcer, with only 4 RCTs (n = 56-210) examining the role of systemic esketamine for cesarean pain but with substantially different study designs, primary outcomes, and esketamine doses . Overall, the studies are, however, promising, suggesting that esketamine is associated with reduced intraoperative pain, reduced postoperative pain, and the need for lower doses of local anesthetic for spinal anesthesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation